Femoral venous access: State of the art and future perspectives - Annetta, Maria Giuseppina; Elli, Stefano; Marche, Bruno; Pinelli, Fulvio; Pittiruti, Mauro (The journal of vascular access, 2025)
In the past 5 years, non-dialysis femoral venous access has changed in terms of indications, techniques of insertion, and expected incidence of complications. To the traditional non-emergency indication for femoral catheters-obstruction of the superior vena cava-many other indications have been added, both in intensive and non-intensive care. The insertion technique has evolved, thanks to ultrasound guided venipuncture, tunneling, and ultrasound based intraprocedural tip location. Insertion of femorally inserted central catheters may be today regarded as a procedure with an extremely low intraprocedural and post-procedural risk. The risk of infection is reduced by the possibility of the exit site at mid-thigh, by the use of cyanoacrylate glue for sealing the exit site, and by appropriate intraprocedural strategies of infection prevention. The risk of catheter-related thrombosis is low, due to several concomitant strategies: a proper match between vein diameter and catheter caliber; an accurate intraprocedural assessment of tip location by ultrasound and/or intracavitary ECG; the consistent use of ultrasound guided venipuncture and micro-introducer kits; an adequate stabilization of the catheter at the exit site. The risk of mechanical complications and the risk of lumen occlusion are minimized when using polyurethane, power injectable catheters. All these novelties have brought a revolution in the field of femoral venous access, so that this route may be considered as safe and effective as other approaches to central venous catheterization.